2010
DOI: 10.1159/000297765
|View full text |Cite
|
Sign up to set email alerts
|

Useless Perinatal Therapies

Abstract: With respect to Professor Bengt Robertson whose research studies were very instrumental in the development of one of the most important and evidence-based therapies in perinatal medicine, namely surfactant therapy, I thought it might be appropriate to review some useless or harmful perinatal therapies. Although the term ‘neonatology’ has only been in existence for about 50 years, care of the newborn in the 19th century was largely provided by nurses and obstetricians. As an example, Pierre Budin, a Parisian ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 139 publications
0
3
0
2
Order By: Relevance
“…As for risk reduction for RDS, in animal models, chorioamnionitis increased the surfactant pool, improved lung compliance, and reduced the risk for RDS. Similar effects on lung maturation were found after intra-amniotic injection of lipopolysaccharides (LPS) [21,51,71,76,111] .…”
Section: Inflammatory Mediators As An Alternative To Gc For Antenatalmentioning
confidence: 72%
“…As for risk reduction for RDS, in animal models, chorioamnionitis increased the surfactant pool, improved lung compliance, and reduced the risk for RDS. Similar effects on lung maturation were found after intra-amniotic injection of lipopolysaccharides (LPS) [21,51,71,76,111] .…”
Section: Inflammatory Mediators As An Alternative To Gc For Antenatalmentioning
confidence: 72%
“…Analysis did not show any treatment benefits but demonstrated higher mortality in infants allocated to receive corticitropin. This seminal study illustrates how the young discipline of neonatology aimed to assess new interventions using a "fair test"; however, many other examples exist where interventions were introduced without supporting trial-based evidence, sometimes with adverse consequences that were not revealed for many years (5). A salutary example is the association of supplemental oxygen with retinopathy of prematurity in preterm infants (6).…”
Section: Origins Of Trial-based Evidencementioning
confidence: 99%
“…Perkütan emilim preterm bebeklerde term bebeklerden çok daha yüksek düzeydedir 1,2,13 . Tablo 2'de yenidoğanda, bir kısmı tıbbi amaçla deriye topikal olarak uygulanan çeşitli etken maddelerin perkütan emilimine bağlı geliştiği rapor edilen istenmeyen durumlar özetlenmektedir 1,2,5,[7][8][9][10][11][12][13]17 . Bununla birlikte pretermlerin term yaşıtlarının epidermal yetilerini yakalaması için gereken 2-3 haftalık sürede var olan yüksek epidermal geçirgenlik teofilin ve diamorfin gibi bazı ilaçların topikal kullanımına imkan vermektedir 1,2,6,15,17 .…”
Section: Perkütan Emilimunclassified
“…Bu dönemde iyatrojenik durumlar dahil çok çeşitli dermatolojik sorun sık olarak yaşanmaktadır. [6][7][8][9][10][11][12] Bu durumun temel nedeni; diğer organ sistemleri ile birlikte derinin anatomik bütünlüğe rağmen henüz matürasyonunu tamamlamamış olmasıdır [3][4][5][6][7][8][9][10][11] . Yenidoğan deri fizyolojisinin iyi bilinmesi, bu dönemde karşılaşılabilecek deriye ait yetersizlikler ve sorunların ön görülebilmesi ile uygun topikal tedavinin seçilmesinin yanı sıra gereksiz ya da zararlı olabilecek topikal uygulamaların önlenmesine katkı sağlayacaktır.…”
unclassified